2022
DOI: 10.4103/jgid.jgid_281_21
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Combined Ivermectin and Zinc Sulfate versus Combined Hydroxychloroquine, Darunavir/Ritonavir, and Zinc Sulfate among Adult Patients with Asymptomatic or Mild Coronavirus-19 Infection

Abstract: Introduction: Ivermectin, hydroxychloroquine (HQ), and darunavir/ritonavir are widely prescribed as an oral treatment for severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection despite their uncertainty of clinical benefit. The objective is to determine the safety and the efficacies of two treatment regimens against SARS-CoV-2 infection. Methods: We conducted an open-labeled, randomized, controlled trial to compare the efficacy between a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Characteristics of included studies are given in Table 1. Seventeen studies 47–63 were excluded as they were not RCTs and we identified 39 ongoing studies 64–102 and 2 studies 103,104 are awaiting classification.…”
Section: Resultsmentioning
confidence: 99%
“…Characteristics of included studies are given in Table 1. Seventeen studies 47–63 were excluded as they were not RCTs and we identified 39 ongoing studies 64–102 and 2 studies 103,104 are awaiting classification.…”
Section: Resultsmentioning
confidence: 99%